THE EFFECT OF DIFFERENT TEMPERATURES ON OIL YIELD OF WHITE-EEL TAILED CATFISH (Paraplotosus albilabris) EXTRACTED WITH DRY-RENDERING METHOD - M. Ufan M. Ufan; Mirna Ilza; Andarini Diharmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACTWhite eel tailed catfish (Paraplotosus albilabris) is a fish that lives in coastal sea or river estuaries, this fish is a carnivorous fish. One way to get fish oil is by extraction. This study aimed to determine the characteristics of the oil and the yield of White-Eel Tailed Catfish. The method used was an experiment using a completely randomized non-factorial design with yield test parameters. The treatments used were different extraction temperatures (50, 60 and 70ºC) with 3 replications. The analysis of results showed the characteristic color of white eel tailed catfish oil with a temperature of 50, 60, 70ºC was dark brown, light brown and alight yellow. The result of analysis of varience of different temperature had a significant effect on the yield of white-eel tailed catfish oil. The results of analysis of the yield of white eel tailed catfish oil at temperatures of 50, 60 and 70οC were 3.01%, 3.43% and 3.67% respectively. The highest yield value of white eel tailed catfish oil exctracted with temperature of 70ºC was 3.67%. Keywords: dry rendering, white eel tailed catfish, Fish Oil, Temperature